The Epidemiology of Cystic Fibrosis in Arab Countries: A Systematic Review - Samer Hammoudeh (3095097) (2022)
Cystic fibrosis (CF) is a genetic autosomal recessive disease that involves multiple systems. Both life quality and expectation are affected by the debilitating multi-system involvement of the disease which includes pulmonary, gastrointestinal, reproductive, and endocrine symptoms. Very few studies have covered the epidemiological aspects of the disease among Arab countries. To systematically review the available epidemiological literature on cystic fibrosis in order to describe the epidemiological state of this disease in the Arab world, this review used PubMed to search for relevant articles related to patients with cystic fibrosis, with no restriction on gender or age. Google scholar and the snowballing technique were used to locate further articles. A total of 17 articles met the inclusion criteria for this review. These articles were from Bahrain, Egypt, Jordan, Kuwait, Morocco, Oman, Saudi Arabia, Tunisia, and the United Arab Emirates. The articles scored 1.5–6.5 out of 8 on the quality assessment. The epidemiological data reported varied based on country and type of study. The establishment of CF registries is definitely a priority in the region, as well as the need for more research involving CF patients particularly those involving the epidemiological and clinical characteristics of these patients. Other Information Published in: SN Comprehensive Clinical Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42399-021-00756-z